2002
DOI: 10.1210/jc.2002-020339
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Aberrations by Comparative Genomic Hybridization in Hürthle Cell Thyroid Carcinomas Are Associated with Tumor Recurrence

Abstract: Hürthle cell thyroid neoplasms are classified as variants of follicular neoplasms, but they have distinct clinicopathological features. Chromosomal aberrations by comparative genomic hybridization (CGH) are common in Hürthle cell neoplasms. However, there is currently only limited information concerning the relationship between the chromosomal aberrations by CGH and tumor behavior. We, therefore, investigated chromosomal aberrations in primary Hürthle cell neoplasms (13 carcinomas and 15 adenomas) using CGH an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
54
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 27 publications
9
54
0
Order By: Relevance
“…Amplification of chromosome 1p36 in oncocytic FA was additionally confirmed by FISH. This is consistent with the report by Wada et al, who also found a gain of chromosome 1p36 in oncocytic FA by CGH analysis [32]. In the current study, we further demonstrated a significant positive correlation between the percentage of tumor cells in FA expressing unstable 53BP1 expression and the percentage of cells positive for the expression of TP73, which is encoded by a gene located on chromosome 1p36.2-3.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Amplification of chromosome 1p36 in oncocytic FA was additionally confirmed by FISH. This is consistent with the report by Wada et al, who also found a gain of chromosome 1p36 in oncocytic FA by CGH analysis [32]. In the current study, we further demonstrated a significant positive correlation between the percentage of tumor cells in FA expressing unstable 53BP1 expression and the percentage of cells positive for the expression of TP73, which is encoded by a gene located on chromosome 1p36.2-3.…”
Section: Discussionsupporting
confidence: 93%
“…This study also revealed a higher incidence of CNA in the tumor DNA of oncocytic FA exhibiting unstable 53BP1 expression, providing further evidence for a role of genomic instability during oncocytic FA tumorigenesis and its association with the pattern of 53BP1 expression. Previous CGH analyses found that chromosomal aberrations were common in oncocytic FA/Hürthle cell adenoma [30][31][32]. Although some studies have found that carcinomas have more chromosomal gains and losses than adenomas, in others the differences were not statistically significant [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analyses revealed similar allelic proportions in the primary tumor and the LN metastases, but highlighted the presence of LOH of the entire chromosome 19 in the PLM. Interestingly, results from several comparative genomic hybridization (CGH) studies have indicated that a gain of chromosome 19 is positively associated with thyroid tumor aggressivity and recurrence, including lung metastases (Tallini et al 1999, Wada et al 2002. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although there are different reports of overexpression of Skp2 protein in human haematological and solid cancers (Gstaiger et al 2001, Kudo et al 2001, Latres et al 2001, Chiarle et al 2002, Masuda et al 2002, Signoretti et al 2002, Li et al 2004, so far there are no studies regarding the clinical significance or the biological behaviour of Skp2 expression in human thyroid carcinomas. Most interestingly, genetic alterations that result in gain of part or of the entire short arm of chromosome 5, where the Skp2 gene has been assigned at 5p13, frequently occur in PTC, Hurthle carcinomas and ATC (Hemmer et al 1999,Wada et al 2002, Foukakis et al 2005, suggesting that Skp2 may be the target of gene amplification in a fraction of thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%